Penentuan Peak Kilovoltage (kVp) Pesawat Sinar-X Dengan Pemanfaatan Imaging Plate (IP) Di RSUD Dr. Moewardi - Bibit Cahyani; Utari Utari; Muhtarom Muhtarom (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2021)
Research has been carried out to determine the kVp of X-ray aircraft using an imaging plate (IP) as a measuring tool. The imaging plate functions to record images after irradiation and as a detector to capture and store X-ray energy when it penetrates an object. The purpose of this study is to use IP as a kVp measurement tool. The method used is to create a characteristic curve of the relationship between the ratio of Region of Interest (ROI) of two aluminum filters to rated voltage (kVp). From the research obtained the equation y = 2816.61 x2 – 4532.19 x + 1878.65 with R2 = 0.988. The kVp test was carried out using a fluoroscopic X-ray model SM-20HFH. The test results obtained that the measured kVp value at a voltage of 70 kV was 66.21 kV and an error value of 5.41%. While the measured kVp value at 55 kV is 58.95 kV with an error value of -7.18%. These results indicate that IP can be used to measure kVp with an error below the allowable tolerance, namely the max error ≤ of 10%.